Pricing Full Deposit Insurance in Germany amidst the Financial Crisis 2008-2010 - Markus R. Kosters; Stefan T.M. Streatmans; Mario Maggi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
This paper investigates the pricing of full deposit insurance in Germany in the context of its political promise by the German government. We implement the characteristics of the mutual guarantee framework of German banks and the specifics of the German deposit insurance system into a Monte Carlo model. The analysis suggests that banks have an incentive to increase their riskiness if they do not have to bear the fair value of the insurance costs of their deposits. On the other hand, the government should incentivise banks to reduce their size and become more specialized to achieve better diversification in the German banking landscape.
Keywords: 330; Asset pricing; financial crisis; deposit insurance; mutual guarantee framework